Technology Support for Distance Learning at Indonesia’s Underdeveloped Regions Universities - Kusumaningrum, Dian; Noviyanti, Anastasia Ary (Program Studi Pendidikan Matematika FMIPA Universitas Negeri Jakarta, 2023)
The Ministry of Education (MoE) provided technology support to strengthen the educational capacity during the COVID-19 Pandemic. MoE’s support include educational tablets (DIKTI Edu), SPADA DIKTI (online platform of distance learning), internet satellite (VSAT), and Mobile VSAT. This research aims to assess the impact of three main aspects: the support of online learning, inequality in access to education, and increasing the quality of lecturers and the learning process. A survey of 657 undergraduate students was conducted based on a purposive stratified sampling in underdeveloped areas from four chosen provinces. Descriptive statistics and a before-after tests were done. Results shows that the devices were received well and has been used as their primary device for distance learning. Moreover, the impact was promising because all three aspects indicated significant positive effects. Nonetheless, the MoE still must tackle some drawbacks:1. Students facing technical barriers feel that improvement in the accessibility to install vital software needed and providing a device with a sim card slot ,for online learning is prominent, 2. Socialization of SPADA DIKTI and access to more relevant materials for broader students is also recommended and 3. In-depth studies on student I.T. awareness and further dynamics of grades should be conducted.